Coping strategies and associated factors among people with physical disabilities for psychological distress in Ethiopia - Getachew Tesfaw Desalegn; Tadele Amare Zeleke; Shegaye Shumet; Yohannes Mirkena; Tilahun Kassew; Dessie Abebaw Angaw; Endalamaw Salelew (BMC, 2023)
Abstract Background Coping strategies are frequently used among individuals with physical disabilities when they face adversities. Low- and middle-income countries are not investigated coping styles among psychological distress persons with disabilities despite the high prevalence of psychological distress. The aim of this study was to identify coping strategies among people with physical disabilities for their psychological distress in Ethiopia has a crucial role to improve the health status of persons with physical disabilities. Methods An institution-based cross-sectional study was employed among individuals living with physical disabilities at the University of Gondar staff and students from May to June 2021. All staff and students with physical disabilities were screened for psychological distress (n = 269). The census sampling technique was used to select the study participants for psychological distress. The Brief Cope with Problems Experienced (COPE-28) was used to assess coping strategies. Bivariate and multivariate linear regression analyses were used to identify factors associated with coping strategies. An odd ratio (OR) with a 95% confidence interval (CI) at P < 0.05 was computed to assess the strength of the association. Results The emotional-focused coping strategy was the most frequently used when dealing with psychological distress among participants with physical disabilities. The most commonly used emotional-focused coping strategy was spirituality. In the multivariate analyses; urban residence (β = 3.05, 95% CI: 0.98, 5.12), and stigma (β = 3.10, 95% CI: 0.61, 2.83) were factors positively associated with emotion-focused coping strategy, and World Health Organization Quality of Life (WHO QOL) (β = 0.18, 95% CI: 0.13, 0.22), and stigma (β = 1.11, 95% CI: 0.61, 2.83) were factors significantly associated with problem-focused coping. Urban residence (β= -0.96, 95% CI: -1.69, -0.22) was negatively associated with dysfunctional coping strategy, but WHO QOL (β = 0.35, 95% CI: 0.32, 0.38) was positively correlated with dysfunctional coping. Conclusion In this study revealed that spirituality is the most frequently used coping strategy among the study participants. Urban residents, stigma, and WHO QOL significantly correlated with coping strategies among such patients. The Ministry of Health, Ministry of Education, and other concerned organizations may find the present findings useful to strengthen the coping styles to minimize psychological distress among people with physical disabilities.